2022
DOI: 10.1088/1755-1315/970/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of optical properties of coals by petrography and spectroscopy methods

Abstract: This paper reports determining the grayscale intensity of macerals in the coal lump polished sections oriented along and across the layering of three main groups of sub-bituminous, high volatile bituminous, low volatile bituminous coals. All measurements have been performed in white, red, yellow, green, blue light. The influence of all selected factors and most of their combinations on grayscale intensity is reliable; the most pronounced effects are established for the optical filter color and the maceral type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The work [9] proposes a new method for determining the degree of metamorphism based on the index of gray shade intensity (GI) for microphoto images of lump sections in coal preparations with subsequent digital computer processing. Subsequently, the spectral characteristics of this method were refined [10]. In these works, the choice of maceral for research (vitrinitis) and the orientation of the observation plane in the preparation (cross-section) were justified, which does not contradict existing standards [11].…”
Section: Introductionmentioning
confidence: 99%
“…The work [9] proposes a new method for determining the degree of metamorphism based on the index of gray shade intensity (GI) for microphoto images of lump sections in coal preparations with subsequent digital computer processing. Subsequently, the spectral characteristics of this method were refined [10]. In these works, the choice of maceral for research (vitrinitis) and the orientation of the observation plane in the preparation (cross-section) were justified, which does not contradict existing standards [11].…”
Section: Introductionmentioning
confidence: 99%
“…To some extent, this is naturally related to the available equipment. Earlier, in work [6], a statistical analysis of the influence of the spectral characteristics of optical and photometric devices used in the proposed method was carried out. The analysis showed that the influence of all selected factors Color, Macerals, Rank, Bedding, as well as most of their combinations, on the GI indicators significant, and the chosen approach is an alternative method for quantifying relative changes in the reflectivity and position of the diffuse spectral minimum without using a micro spectrometer.…”
Section: Introductionmentioning
confidence: 99%